A transdisciplinary review and framework of consumer interactions with embodied social robots: Design, delegate, and deploy - Marah Blaurock; Martina Čaić; Mehmet Okan; Alexander P. Henkel (International Journal of Consumer Studies, 2022)
Social robots are gradually entering the organizational frontline, and research is beginning to unveil the implications for consumer–firm interactions. While empirical studies on human–robot service interaction (HRSI) are scarce in business literature, other scientific fields have generated an abundance of empirical findings that can inform consumer research on successfully integrating embodied social robots in consumer-facing services. In this light, a systematic literature review was conducted across scientific fields, screening over 13,500 research articles. Through a thorough review process, 199 service-relevant empirical research articles were identified. Emanating from these data, an organizing meta-framework is advanced (D3: design, delegate, and deploy). Leveraging this D3 framework, a comprehensive overview of several dimensions of the literature is provided, and key insights for each framework dimension are presented. Based on this overview, implications for whether, how, and when to integrate social robots in practice and a comprehensive future research agenda are developed.
Keywords: 330; consumers; embodied social robots; future research agenda; human–robot service interactions; systematic literature review